Targeting thyroid cancer microenvironment and epigenetic signalling: new frontiers in cancer endocrinology basic and clinical research - Carmelo Nucera (Frontiers Research Topics, 2014)
This Research Topic is devoted to the understanding of molecular mechanisms of Human Thyroid Cancers. Original research describing functional studies of genetic mutations that shed novel insights into the aetiology and pathogenesis of these cancers, as well as angiogenesis and tumor microenvironment, mouse models studies that describe mechanisms or novel potential therapeutic targets and biomarkers for these endocrine cancers are presented. Scopes: The scope of this Research Topic was to cover the entire field of thyroid cancers: the main focus of this topic is translational, with an emphasis on bench to bedside research. Experimental, pre-clinical and clinical research addressing the following aspects is included in this Research Topic: 1) Investigation of specific molecular patterns of thyroid tumorigenesis, which could allow the development of new directions in the field of pharmacotherapy research; 2) Emphasis on animal studies (preclinical models of human anaplastic thyroid cancers) for the validation of biomarkers with the potential to lead to clinical trials, and studies of targetable mechanisms of oncogenesis, progression of these malignancies, tumor microenvironment and extracellular matrix, and metastatic disease; 3) Assessment of biomarkers to predict the potential response or resistance to drug treatment (targeted cancer therapies) or to guide the follow-up of treated patients; 4) Investigation of new laboratory molecular tests (e.g. molecular techniques and applications of thyroid fine-needle aspiration biopsy) to translate in the clinical practice; In summary, specific areas of interest include: thyroid cancer genetics; genome-wide analysis; clinical and translational research; orthotopic mouse models of metastatic thyroid carcinoma; tumor microenvironment; epigenetic; biological insights of personalized medicine; novel applications of bioinformatics; large scale molecular characterization of tumors; diagnostic or prognostic biomarkers; endocrine pathology studies; thyroid fine-needle aspiration.